AG‐exclusion zone revisited: Lessons to learn from 91 intronic NF1 3′ splice site mutations outside the canonical AG‐dinucleotides. Issue 6 (11th March 2020) - Wimmer, Katharina; Schamschula, Esther; Wernstedt, Annekatrin; Traunfellner, Pia; Amberger, Albert; Zschocke, Johannes; Kroisel, Peter; Chen, Yunjia; Callens, Tom; Messiaen, Ludwine
Abstract: Uncovering frequent motives of action by which variants impair 3′ splice site (3′ss) recognition and selection is essential to improve our understanding of this complex process. Through several mini‐gene experiments, we demonstrate that the pyrimidine (Y) to purine (R) transversion NM_000267.3( NF1 ):c.1722‐11T>G, although expected to weaken the polypyrimidine tract, causes exon skipping primarily by introducing a novel AG in the AG‐exclusion zone (AGEZ) between the authentic 3′ss AG and the branch point. Evaluation of 90 additional noncanonical intronic NF1 3′ss mutations confirmed that 63% of all mutations and 89% (49/55) of the single‐nucleotide variants upstream of positions ‐3 interrupt the AGEZ. Of these AGEZ‐interrupting mutations, 24/49 lead to exon skipping suggesting that absence of AG in this region is necessary for accurate 3′ss selection already in the initial steps of splicing. The analysis of 91 noncanonical NF1 3′ss mutations also shows that 90% either introduce a novel AG in the AGEZ, cause a Y>R transversion at position ‐3 or remove ≥2 Ys in the AGEZ. We confirm in a validation cohort that these three motives distinguish spliceogenic from splice‐neutral variants with 85% accuracy and, therefore, are generally applicable to select among variants of unknown significance those likely to affect splicing. Abstract : Our analysis of the largest number ( n  = 91) of noncanonical 3′ splice site mutations found in a single gene by using an unbiased RNA‐based mutation analysis approach shows that interruption of the AG‐exclusion zone is the major motive of action of these mutations. In a validation cohort we show that this and two additionally identified motives of action distinguish spliceogenic from splice‐neutral variants with 85% accuracy. Therefore, these three motives are generally applicable to select among intronic variants of unknown significance, even when located upstream of position ‐12, those likely to affect splicing.